Local knowledge spillovers and innovation persistence of firms - Adelheid Holl; Bettina Peters; Christian Rammer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
Recent empirical evidence has shown that firm's innovation behavior exhibits high persistency but not much is known about potential contingencies affecting the degree of persistence. This paper focuses on the role of the local knowledge environment and asks how local knowledge spillovers affect firms' innovation persistence. The empirical analysis draws upon a representative panel data set of firms in Germany from 2002-2016, complemented by detailed geographic information of patent activity over discrete distances to proxy local knowledge spillovers. Based on correlated random effects probit models that control for state dependence, unobserved individual heterogeneity and endogenous initial conditions, our results corroborate former evidence that persistency in innovation is driven by true state dependence. More importantly, we find that the local patenting activity positively moderates firms' degree of persistency in innovation behavior. This is a novel firm-level mechanism that can explain the widening of spatial disparities in innovation performance. Estimations with different distance bands show that the strength of knowledge spillovers that contribute to innovation persistence via true state dependence declines rather rapidly with increasing distance.
Keywords: O31; R1; D22; 330; innovation; persistence; location; knowledge spillovers